Exploring vocational students' satisfaction with online learning - Rahyasih, Yayah; Wijaya, Widia Murni; Syarifah, Liah Siti (Journal of Education and e-Learning Research, 2023)
This study aimed to explore the factors that influence vocational students' perceptions of their online learning experiences and assess the quality of online learning that has an impact on student satisfaction. This research used structural equation modeling and partial least square (PLS-SEM) analysis. The purposive sampling technique was chosen to determine the sample of respondents. A total of 3206 students who participated in online learning from various vocational schools in Indonesia filled out an online survey. The results indicate that communication, digital media, interaction, facilities and tutorials have a direct effect on the quality of online learning. Schools that offer online education must prioritize the essential factors required for successful implementation to ensure that students have an enjoyable online learning experience. Teachers should focus on improving the quality of online learning to increase student satisfaction with it. Furthermore, teachers should consider the findings of this research when developing strategies for vocational education in online settings.